Microwave-Assisted Aminoalkylation of Phenols via Mustard Carbonate Analogues - Viviano, Monica; Trapasso, Giacomo; Annatelli, Mattia; Milite, Ciro; Castellano, Sabrina; Aricò, Fabio (Synthesis, 2022)
A microwave-assisted chlorine-free direct phenol substitution is presented, which is indicated as a key green chemistry research area for pharmaceuticals manufacturers. The reaction of β-aminocarbonates (mustard carbonates) with several substituted phenols in the presence of a polar solvent (acetonitrile or butanol) led to the related aminoalkylated products via the anchimeric assistance of the nitrogen incorporated in the organic carbonate backbone. The aminoalkylation required short reaction time (7 min) and the related products were isolated in high yields (>90%) via quick liquid-liquid extraction or column chromatography depending on the solvent employed. Furthermore, microwave irradiation also promoted the one-pot aminoalkylation of phenol in excellent yield. In this approach a β-aminoalcohol was reacted with phenol in the presence of diethyl carbonate, used for the in situ formation β-aminocarbonate, key intermediate in the consequent anchimerically driven alkylation. The resulting product, namely N,N-dimethyl-2-phenoxyethanamine, was isolated as pure in almost quantitative yield.
Keywords: alkylation; green chemistry; phenols; neighboring group effects; dialkyl carbonate; microwave chemistry